‘n Kerk wat getuig, is ‘n kerk wat leef. ‘n Ekklesiologiese perspektief op die missionêre karakter van die kerk - Deel II - Dreyer, D. J. (Verbum et ecclesia, 2004)
In the first of these two articles we focused on the Biblical perspective of the missionary church. The focus in the second article is on the ecclesiology. It is essential to remember that the church is rooted in the kingdom of God. Jesus Christ himself and his ministry was the beginning of the kingdom of God (Mark 1:15). The church exists not for her own sake, but for the world for whom Jesus was crucified. This is the vantage point for a missionary church at the end of the Christendom paradigm. The missionary character of the church (the church as an apostolic church) and eschatology were not always in die focus of the theology of the reformed churches in the Western world. Of the four notes or marks of the church as one, holy, catholic and apostolic, apostolic is the norm for the other three. Apostolicity is a precondition and a result for the church as a missionary church. The message of a missionary church is the only real answer in the search for meaning in this world.